CONCEPTUAL ANALYSIS OF CAUSATION IN LEGAL DISCOURSE - Adam Dolezal; Tomas Dolezal (European Scientific Journal, ESJ, 2014)
This article deals with the conception of causation in legal discourse. Authors firstly examine causation in the scientific, philosophical and common-sense discourse. Does it make sense to use general causal terms when examining causality in law? We can ask whether legal causality isn´t only artificial construct, legal fiction of a causal relationship. Some authors claim that legal causation is not essentially a causation in the true common sense and thus only a pragmatic political decision regarding the application of distributive and corrective justice, and economic evaluation of benefits in society, others on the contrary point out that causality in law as such is equal to its common everyday use or even in the scientific sense. What are the criteria in the legal sense that lead us to judge that certain event causes harm? Which issues relevant to philosophical discourse may be in legal discourse ignored as irrelevant? The authors show the necessary connection between terms causality in different branches although they conclude that causality is pluralistic concept. The issue of this article is to find out solution for causal connection in particular paradigmatic cases and set up some causal formulas that could be used in legal practice.